LncRNA-HIT Functions as an Epigenetic Regulator of Chondrogenesis through Its Recruitment of p100/CBP Complexes. - Hanqian L Carlson; Jeffrey J Quinn; Yul W Yang; Chelsea K Thornburg; Howard Y Chang; H Scott Stadler (PLoS Genetics, 2015)
Gene expression profiling in E 11 mouse embryos identified high expression of the long noncoding RNA (lncRNA), LNCRNA-HIT in the undifferentiated limb mesenchyme, gut, and developing genital tubercle. In the limb mesenchyme, LncRNA-HIT was found to be retained in the nucleus, forming a complex with p100 and CBP. Analysis of the genome-wide distribution of LncRNA-HIT-p100/CBP complexes by ChIRP-seq revealed LncRNA-HIT associated peaks at multiple loci in the murine genome. Ontological analysis of the genes contacted by LncRNA-HIT-p100/CBP complexes indicate a primary role for these loci in chondrogenic differentiation. Functional analysis using siRNA-mediated reductions in LncRNA-HIT or p100 transcripts revealed a significant decrease in expression of many of the LncRNA-HIT-associated loci. LncRNA-HIT siRNA treatments also impacted the ability of the limb mesenchyme to form cartilage, reducing mesenchymal cell condensation and the formation of cartilage nodules. Mechanistically the LncRNA-HIT siRNA treatments impacted pro-chondrogenic gene expression by reducing H3K27ac or p100 activity, confirming that LncRNA-HIT is essential for chondrogenic differentiation in the limb mesenchyme. Taken together, these findings reveal a fundamental epigenetic mechanism functioning during early limb development, using LncRNA-HIT and its associated proteins to promote the expression of multiple genes whose products are necessary for the formation of cartilage.